2007
DOI: 10.1002/casp.916
|View full text |Cite
|
Sign up to set email alerts
|

Dual pathways to engage in ‘Silent Marches’ against violence: moral outrage, moral cleansing and modes of identification

Abstract: A survey (N ¼ 120) examined variables that contribute to the willingness of people to engage in silent marches against violence in the Netherlands. As argued in Sacred Value Protection Model (SVPM) of Tetlock, Kristel, Elson, Green, and Lerner (2000) and moral mandate theory of Skitka, Bauman, and Sargis (2005), moral threats that are triggered by violent incidents, may indeed drive people to protest against such incidents. Our findings indicated dual pathways to such protests, that are all associated with rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…Past evidence has found that social inequalities and unfairness can provide the motivation to act for modifying the status quo (e.g., Lodewijkx et al 2008). However, we argue that perceived unfairness also can have the opposite effect (i.e., leading to less civic engagement) depending on the characteristics of the setting.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Past evidence has found that social inequalities and unfairness can provide the motivation to act for modifying the status quo (e.g., Lodewijkx et al 2008). However, we argue that perceived unfairness also can have the opposite effect (i.e., leading to less civic engagement) depending on the characteristics of the setting.…”
Section: Discussionmentioning
confidence: 49%
“…In some cases, studies have obtained contradictory results. For example, there is evidence that the perception of inequality may represent a trigger for civic actions, in order to modify social inequalities (Montada and Schneider 1989); on the other hand, there is evidence that belief in a just world is positively associated to civic behaviors, such as volunteering (e.g., Lodewijkx et al 2008). To our knowledge, no studies to date have explained the mechanisms accounting for the positive association between perceived fairness and civic engagement.…”
Section: Gaps In the Current Research Literaturementioning
confidence: 99%
“…Consensual issues root in suddenly imposed grievances to evoke a communal sense of repulsion and indignation. Examples in place are the death of a child caused by drunk-driving (McCarthy & Wolfson, 1996) or senseless violence (Lodewijkx, Kersten & Van Zomeren, 2008). Such tragic events put consensual issues crudely at the top of public and political agendas, and discussions easily converge on a general standpoint.…”
Section: Mobilization With Minimal Organizationmentioning
confidence: 99%
“…Sample items are: "I don't mind working hard today-knowing that I will eventually be rewarded by my supervisor," "There is a lot of give and take in the relationship with my supervisor" (1 = strongly disagree, 5 = strongly agree; M = 3.15, SD = .91, α = .92). We measured deontic anger with a four-item scale (Lodewijkx, Kersten, & Van Zomeren, 2008). Sample items are "Do you find your supervisor's behavior immoral?…”
Section: Nostalgia and Justice 26mentioning
confidence: 99%